Comparisons Between Upper and Lower Extremity Deep Vein Thrombosis: A Review of the RIETE Registry. (October 2017) - Cote, Lauren P.; Greenberg, Steven; Caprini, Joseph A.; Tafur, Alfonso; Choi, Chris; Muñoz, Francisco J.; Skride, Andris; Valero, Beatriz; Porras, José Antonio; Ciammaichella, Maurizio; Hernández-Blasco, Luis Manuel; Monreal, Manuel; et al.
Background: The outcome of patients with upper extremity deep vein thrombosis (UEDVT) has not been consistently compared with that in patients with lower extremity deep vein thrombosis (LEDVT). Methods: We used the Registro Informatizado de Enfermedad Trombo Embólica (RIETE) registry to compare the outcomes during the course of anticoagulant therapy in patients with UEDVT versus outcomes in patients with LEDVT. Results: As of August 2015, 37, 366 patients with acute DVT had been enrolled in RIETE: 35094 (94%) had LEDVT, 1334 (3.6%) non-catheter related UEDVT (672 unprovoked and 662 provoked) and 938 (2.5%) had catheter-related UEDVT. During the course of anticoagulation, patients with unprovoked UEDVT had a higher rate of DVT recurrences (hazard ratio [HR]: 2.22; 95% CI: 1.37-3.43) and a similar rate of PE recurrences or major bleeding than those with unprovoked LEDVT. Patients with non-catheter-related provoked UEDVT had a similar outcome than those with provoked LEDVT. Among patients with UEDVT, those with non-catheter related unprovoked UEDVT had a lower rate of PE recurrences (HR: 0.06; 95% CI: 0-0.35) and major bleeding (HR: 0.20; 95% CI: 0.08-0.46) than those with catheter-related UEDVT or those with non-catheter related provoked UEDVT (HR: 0.10; 95% CI: 0.004-0.60; and 0.22; 95% CI: 0.08-0.52, respectively). On multivariable analysis, any difference had disappeared. Conclusion: During the course of anticoagulation, patients with UEDVT had a similar outcome than those with LEDVT. Among UEDVT patients, there were some differences according to the presence of catheter or additional risk factors for DVT. These differences disappeared after adjusting for potentially confounding variables.